Peningkatan Minat Dan Hasil Belajar Matematika Melalui Penerapan Strategi Index Card Match Pada Siswa Kelas IV SD Negeri Muncar 02 Tahun Ajaran 2015/2016 - Widiatmoko, Imam Darwis; , Dra. Risminawati, M.Pd (2016)
This type of research is the Classroom Action Research (PTK). Desain research conducted starting of planning, implementation, data collection and analyzing data. The data collection technique using the technique of interview, observation techniques, test engineering and documentationThe purpose of this study is Increasing interest in learning through the application of learning strategies Index Card Match in grade IV students of SD Negeri Muncar 02 Kecamatan Susukan Academic Year 2015/2016. And to improve learning outcomes through the application of learning strategies Index Card Match in grade IV students of SD Negeri Muncar 02 Kecamatan Susukan Academic Year 2015/2016. Based on the results of Class Action Research conducted in the learning of mathematics in two cycles can be concluded that through the application of learning strategies Index Card Match can increase interest and mathematics learning outcomes Elementary School fourth grade students Muncar 02 Susukan District of Semarang District Academic Year 2015/2016. This was evident at prasiklus student interests only 36.25%. In the first cycle students' interest increased to 48.00%. While on the second cycle the student's interest increased to 86.65%. After the implementation of the action in the second cycle, mastery learning outcomes of students has increased. If the prasiklus completeness of student learning outcomes is only 27.3%, then in the first cycle increased to 50%, the second cycle mastery learning outcomes of students increased to 86.3% in grade IV students of SD Negeri Muncar 02 Kecamatan Susukan Academic Year 2015 / 2016.